Innovation Work Behavior as Mediator of Social Support and Engagement on Performance: Perilaku Inovasi sebagai Mediator Dukungan Sosial dan Keterlibatan terhadap Kinerja - Prayogi Wicaksono; Arik Susbiyani; Amalina Maryam Zakiyyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Public service innovation represents a vital element in strengthening governance effectiveness, particularly within regional early warning systems. Specific Background: In Banyuwangi Regency, the Sistem Deteksi Dini Kewaspadaan Daerah (SIDEDIWASDA) application aims to digitalize conflict vigilance reporting, yet disparities in operator performance persist due to limited social support and engagement. Knowledge Gap: Despite studies linking social support and work engagement to performance, few have examined Innovation Work Behavior (IWB) as a mediating factor within technology-based governance settings. Aims: This study investigates the direct and indirect effects of social support and work engagement on operator performance, with IWB as a mediator. Results: Using data from 124 respondents analyzed via SEM–WarpPLS, findings reveal that social support (β=0.298; p=0.001) and work engagement (β=0.249; p=0.001) significantly enhance performance, both directly and through IWB (β=0.346; p=0.001). Novelty: The study introduces an integrated behavioral model linking psychological and innovative aspects of operators within a public-sector digital system. Implications: These results highlight the importance of continuous capacity-building and teamwork culture to optimize digital governance implementation and elevate civic service quality. Highlights: IWB mediates the link between social support and performance. SEM–WarpPLS confirms all variables significantly influence outcomes. Promotes continuous training and teamwork in digital governance. Keywords: Social Support, Work Engagement, Innovation Work Behavior, Operator Performance, Digital Governance